2007
DOI: 10.1104/pp.107.108712
|View full text |Cite
|
Sign up to set email alerts
|

Powdery Mildew Induces Defense-Oriented Reprogramming of the Transcriptome in a Susceptible But Not in a Resistant Grapevine

Abstract: Grapevines exhibit a wide spectrum of resistance to the powdery mildew fungus (PM), Erysiphe necator (Schw.) Burr., but little is known about the transcriptional basis of the defense to PM. Our microscopic observations showed that PM produced less hyphal growth and induced more brown-colored epidermal cells on leaves of PM-resistant Vitis aestivalis 'Norton' than on leaves of PM-susceptible Vitis vinifera 'Cabernet sauvignon'. We found that endogenous salicylic acid levels were higher in V. aestivalis than in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
236
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(274 citation statements)
references
References 74 publications
34
236
4
Order By: Relevance
“…The powdery mildew regulated VvNAC36 transcription factor gene may have positive role in defense system against powdery mildew infection. As the previous microarray study indicated, the high expression of VvNAC36 transcription factor gene was only regulated by powdery mildew and not by exogenous salicylic acid treatment [14]. This study identified the responsible motif for regulation of this gene, the GT-1 box, which is regulated by elicitor not by salicylic acid.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The powdery mildew regulated VvNAC36 transcription factor gene may have positive role in defense system against powdery mildew infection. As the previous microarray study indicated, the high expression of VvNAC36 transcription factor gene was only regulated by powdery mildew and not by exogenous salicylic acid treatment [14]. This study identified the responsible motif for regulation of this gene, the GT-1 box, which is regulated by elicitor not by salicylic acid.…”
Section: Discussionmentioning
confidence: 78%
“…For instance VvNAC18, VvNAC29, VvNAC37, VvNAC65 and VvNAC70 were expressed at high levels at inflorescence; VvNAC26 plays key roles in response to abiotic stress; in biotic stress response 7 VvNAC increased expression after virus-infection and 10 were up-regulated after Bois noir infection [1]. In addition 7 VvNAC transcription factor genes have been up regulated by powdery mildew elicitor at different levels in the given hour post infection (phi) [14]. Among these 7 transcription factor genes VvNAC36 has been significantly up regulated by powdery mildew infection.…”
Section: Introductionmentioning
confidence: 99%
“…Relationships between grape variety and the abundance of yeast (35,36) and bacterial species (37) on berry surfaces have been documented previously on very limited scales, but not statistically demonstrated. Cultivar differences in growth habit and stress and invasion response (38) could explain how Vitis manages (or incurs) its grape-surface microbial ecosystems, explaining both the "normal" microbiota and cultivar-specific susceptibilities to disease pressures under different environments. Many of the observed patterns support this hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…3A and SI Appendix). Although a decrease in photosynthesis-associated gene expression had previously been observed in whole leaves in response to PM (4,7,11), our focus at the site of infection allowed us to identify a more extensive set of altered photosynthesis-related genes. It also eliminated potential complications associated with differential PM-induced impacts on photosynthesis at the site of infection compared with nearby or distal sites.…”
Section: Pm Site-specific Profiling Supports Diminished Photosynthesimentioning
confidence: 99%